Suppressing supercooling in magnesium nitrate hexahydrate and evaluating corrosion of aluminium alloy container for latent heat storage application - Honcová, Pavla; Pilař, Radim; Danielik, Vladimir; Soska, Peter; Sádovská, Galina; Honc, Daniel (Springer, 2017)
The repeating of heating/cooling cycle (75 times) simulating the heat energy storage in magnesium nitrate hexahydrate confirmed supercooling of 27 K, and thus many non-isostructural nucleating agents were tested in concentration of 1 mass% in four charge/discharge cycles. From the whole group, four promising nucleating salts were subjected to detailed study with addition of 0.5, 1, and 2 mass% of nucleating salt. The results show that the addition of Mg(OH)(2), BaO, MgO and Sr(OH)2 suppressed supercooling below 5 K during 50 melting/crystallization cycles. At the similar conditions (temperature range and repeating of heating and cooling), MNH and MNH with 0.5 mass% Mg(OH)(2) or Sr(OH)2 underwent corrosion tests in aluminium alloy tubes to discover applicability of this material for the containers or capsules for heat storage. The long-term contact (> 49 days) of aluminium alloy with melted heat storage material for 664 h provided information about suitability of alloy for storing of magnesium nitrate hexahydrate with nucleating agent.
Potlačení podchlazení v hexahydrátu dusičnanu hořečnatého a stanovení korozních vlastností hliníkových nádob pro uplatnění při akumulaci tepla
Keywords: Magnesium nitrate hexahydrate; Supercooling; Nucleating agent; Corrosion; Thermal stability; Dusičnan hořečnatý hexahydrát; Podchlazení; Nukleační činidlo; Koroze; Teplotní stabilita